2018
DOI: 10.1002/jhbp.543
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic comparison of the 7th and 8th editions of the American Joint Committee on Cancer staging system for intrahepatic cholangiocarcinoma

Abstract: The 8th edition of the AJCC staging system appears to provide high prognostic contrast for T stage categories, except for T3. However, overall prognostic performance of the 8th edition was not markedly improved over the 7th edition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 28 publications
1
56
1
Order By: Relevance
“…Ahn et al [30] retrospectively analyzed 292 R0-resected ICC patients and the univariate and multivariate survival analyses of OS showed PNI as an independent significant risk factor against long-term survival, which is consistent with our results. However, some studies revealed quite different results that did not support PNI as one [31,32]. Comparatively speaking, fewer studies report the meaning of PNI to RFS.…”
Section: Discussionmentioning
confidence: 96%
“…Ahn et al [30] retrospectively analyzed 292 R0-resected ICC patients and the univariate and multivariate survival analyses of OS showed PNI as an independent significant risk factor against long-term survival, which is consistent with our results. However, some studies revealed quite different results that did not support PNI as one [31,32]. Comparatively speaking, fewer studies report the meaning of PNI to RFS.…”
Section: Discussionmentioning
confidence: 96%
“…The prognostic performance of the 8th edition was overall not markedly improved over the 7th edition based on several validation studies, and potential modifications have been proposed. [17][18][19][20] Interestingly, although one study from a Korean group concluded that the new T3 did not provide good prognostic contrast, 17 a much larger study across 14 major hepatobiliary centers worldwide found the new T3 and stage III to stratify the risk of death for ICC patients. 20 On the other hand, a Japanese group found significant overlaps between T2, T3, and T4 on 5-year disease-specific survival rate, and the authors suggested modifying the size cutoff point at 2 cm for T1 (T1, size 2 cm without other factors; T2, size .2 cm without other factors), and keeping periductal infiltrating in T4 because of its prognostic significance.…”
Section: Carcinoma Of the Intrahepatic Bile Ductmentioning
confidence: 99%
“…A wide variety of prognostic algorithms had been proposed for ICC patients over the years. The prognostic reliability and usability of TNM stage have been questioned (5,6), and other scoring systems were established including Liver Cancer Study Group of Japan (7), Okabayashi et al (8), and Nathan et al (9). Besides, all these staging systems were based solely on variables limited to features of the primary tumor, and there remains a poor ability to predict prognosis for post-operative recurrence ICC patients, while the post-recurrence survival (PRS) of ICC patients is highly heterogeneous, and substantially impacted by features of recurrence and treatment modalities for recurrence (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%